Studies on the Photoinduced Interaction between Zn(II) Porphyrin and Colloidal TiO2 - Heyong Huang; Jiahong Zhou; Yan Zhou; Yanhuai Zhou; Yuying Feng (International Journal of Photoenergy)
The interaction of Zn(II) porphyrin (ZnPP) with colloidal TiO2 was studied by absorption and fluorescence spectroscopy. The fluorescence emission of ZnPP was quenched by colloidal TiO2 upon excitation of its absorption band. The quenching rate constant (kq) is 1.24×1011 M−1 s−1. These data indicate that there is an interaction between ZnPP and colloidal TiO2 nanoparticle surface. The quenching mechanism is discussed on the basis of the quenching rate constant as well as the reduction potential of the colloidal TiO2. And the mechanism of electron transfer has been confirmed by the calculation of free energy change (ΔGet) by applying Rehm-Weller equation as well as energy level diagram.